Intraspecific trophic variation during the early chick-rearing period in Magellanic penguins Spheniscus magellanicus: Influence of age and colony location - Dodino, Samanta Graciela; Riccialdelli, Luciana; Polito, Michael J.; Pütz, Klemens; Raya Rey, Andrea Nélida (Marine Biology)
Intraspecific competition for food resources has the potential to be high for central-place foragers such as penguins and can result in spatial and dietary foraging niche segregation among individuals of the same species. We sampled adults, chicks, and juvenile individuals’ whole blood from three colonies of Magellanic penguins (Spheniscus magellanicus) from Tierra del Fuego along an inshore-offshore corridor. We analyzed the isotopic niche, the trophic position and the diet composition in penguins to investigate intraspecific trophic niche variation in relation to biological (age of individuals) and external factors (foraging habitats, colony location) using carbon (δ13C) and nitrogen (δ15N) stable isotope values. We found isotopic niche segregation between age classes within each colony. When comparing across colonies, only juvenile exhibited some degree of isotopic niche overlap among colonies. In addition, at all three colonies juveniles had the largest isotopic niches with relatively higher variation in δ13C values. All individuals consumed low trophic position (TP) prey items such as the pelagic form of Munida gregaria based on stable isotope mixing model results. Adults and juveniles incorporated high TP (silverside and nototheniids) prey items into their diets, except for juveniles from Martillo Island whose proportions mirror chicks’ values. These results denote that parents consumed different prey items for themselves than for their chicks. Intraspecific trophic niche partitioning between colonies showed a decreasing δ13C and δ15N values from the nearest inshore colony relative to the farther offshore colonies. Understanding within and between colonies foraging strategies are important to set up connectivity between populations, status of the different colonies, and to develop adequate conservation actions. Fil: Dodino, Samanta Graciela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Riccialdelli, Luciana. Consejo Nacional ...